PERBEDAAN PENURUNAN TROMBOSIT PADA DEMAM BERDARAH DENGUE DERAJAT I DAN II DI RS BHAYANGKARA TRIJATA - Putu Diani Wirayanti; I Wayan Putu Sutirta Yasa (E-Jurnal Medika Udayana, 2015)
THE DIFFERENCES  DECREASING PLATELET IN DENGUE HEMORRHAGIC FEVER GRADE I AND II AT BHAYANGKARA TRIJATA HOSPITALDengue hemorrhagic fever was presented by thrombocytopenia with hemoconcentration. The infectious disease caused by dengue virus which is transmitted by the bite of Aedes Aegypti. The degree of severity of dengue hemorrhagic fever is divided into four, namely grade I, II, III, and IV. This study aims to see the mean count of platelets in patients with dengue hemorrhagic fever grade I and II in Bhayangkara Trijata Hospital. Design of the study used cross sectional with study hipotesis is the decreasing platelet count of dengue hemorrhagic fever grade II higher than grade I in Trijata Bhayangkara Hospital. The data was took from the medical records of patients whom were diagnosed with dengue fever by a doctor at the Bhayangkara Trijata Hospital since June 2012 until October 2013. The study result showed the mean of platelet count in dengue hemorrhagic fever grade I was 103.000/mm3 and mean of platelet count dengue hemorrhagic fever grade II was 94.000/mm3. The independent sample t - test obtained p value = 0.244 then is obtained no significant results.